2019
DOI: 10.1145/3218279
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating GSD-Aware

Abstract: Global Software Development (GSD) is currently a strong industry trend. This means that if computer science engineers are to be trained to deal with this model, it is very important to include the topic in software engineering courses, attempting to ensure that students learn about GSD and become familiar with its advantages and challenges. However, software engineering courses do not always consider including it in their curricula. It must also be recognized that it is difficult to find a suitable method to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…Kayworth and Leidner 2000;Powell, Piccoli, and Ives 2004), such studies have failed to provide a comprehensive understanding of how GVT issues impact the effectiveness of specific coordination mechanisms (Nguyen-Duc, Cruzes, and Conradi 2015). Thus, researchers argue that existing studies shed little light on the practicalities of implementing effective coordination in GVTs (Espinosa et al 2007;Taweel et al 2009;Vizcaíno et al 2019) as the challenge of coordinating ICT-enabled work in GVTs has not been adequately addressed (cf. Dubé and Robey 2009;Medappa and Srivastava 2019;Watson-Manheim, Chudoba, and Crowston 2012).…”
Section: Background and Prior Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Kayworth and Leidner 2000;Powell, Piccoli, and Ives 2004), such studies have failed to provide a comprehensive understanding of how GVT issues impact the effectiveness of specific coordination mechanisms (Nguyen-Duc, Cruzes, and Conradi 2015). Thus, researchers argue that existing studies shed little light on the practicalities of implementing effective coordination in GVTs (Espinosa et al 2007;Taweel et al 2009;Vizcaíno et al 2019) as the challenge of coordinating ICT-enabled work in GVTs has not been adequately addressed (cf. Dubé and Robey 2009;Medappa and Srivastava 2019;Watson-Manheim, Chudoba, and Crowston 2012).…”
Section: Background and Prior Workmentioning
confidence: 99%
“…Leadership and knowledge sharing were excluded from the study to focus instead on GVT issues that have been predominantly reported as having a direct, negative impact on coordination (Noll, Beecham, and Richardson 2010;Palacio et al 2011). Geographical distance hampers the effectiveness of coordination measures that typically rely on the proximity of team members (Vizcaíno et al 2019). Similarly, time zone differences disrupt the typical coordination processes that ensure team members successfully interact to ensure a successful project outcome (Espinosa and Carmel 2003).…”
Section: Towards a Conceptual Model For Studying The Coordination Of Virtual Teamsmentioning
confidence: 99%
See 3 more Smart Citations